Advancing Sustainability Through Green Public Procurement: A Comprehensive Analysis - Ahmari, Dhafer Al; Brika, Said K. (Journal of Ecohumanism, 2024)
Greener Supply Initiatives acquisitions have received much focus from researchers, policymakers, and practitioners all over the world in the last four decades as a new approach for green public procurement. GPP practices and policies motivate the consideration of environmental criteria in the government buying processes. The present study attempts to put GPP into a historical perspective of research evolution by conducting a bibliometric analysis for public procurement, using 704 publications obtained from the Scopus database. Content and network analyses allow us to determine the existing thematic clusters, outstanding authors, and trends, as well as gaps in this developing area. The findings of this research suggest that the need to do research in this area has been gradually rising, and studying the effects of GPP on environmental management, principles of the circular economy, and sustainable development goals are among the major milestones made. It further explains the nature of the interaction that exists between the publish and perish brackets, that is, the academia, the industry, and the government. In order to provide a framework and context for GPP research, the authors also investigate which of the most cited papers references each other. The results open and outline a number of avenues for future research, such as the combination of digital information technologies and GPP processes and the inter-sectoral angles. This knowledge is beneficial both for scholars and practitioners, making it possible to propose more creative ways of fully exploiting the opportunities offered by green public procurement practices. This paper contributes to existing knowledge instead of being the last word on the subject and simultaneously offers possibilities for cross-disciplinary research on green public procurement and its importance in attaining the goals of sustainable public procurement.